2020
DOI: 10.1371/journal.pone.0236370
|View full text |Cite
|
Sign up to set email alerts
|

Care complexity individual factors associated with adverse events and in-hospital mortality

Abstract: Introduction Measuring the impact of care complexity on health outcomes, based on psychosocial, biological and environmental circumstances, is important in order to detect predictors of early deterioration of inpatients. We aimed to identify care complexity individual factors associated with selected adverse events and in-hospital mortality. Methods A multicenter, case-control study was carried out at eight public hospitals in Catalonia, Spain, from January 1, 2016 to December 31, 2017. All adult patients admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 56 publications
(84 reference statements)
1
14
0
7
Order By: Relevance
“…The in-hospital mortality observed in this study was 2.7%. Previous literature reported the in-hospital mortality of 1 to 5% [5,[23][24][25][26], with two multicenter studies reporting rates 2.2% [5,23], our result is consistent with previous literature. Identifying predictor factors for pneumonia in patients is crucial in clinical decision making The death of frail elderly with pneumonia is not frequently only due to pneumonia itself [5,30].…”
Section: Discussionsupporting
confidence: 93%
“…The in-hospital mortality observed in this study was 2.7%. Previous literature reported the in-hospital mortality of 1 to 5% [5,[23][24][25][26], with two multicenter studies reporting rates 2.2% [5,23], our result is consistent with previous literature. Identifying predictor factors for pneumonia in patients is crucial in clinical decision making The death of frail elderly with pneumonia is not frequently only due to pneumonia itself [5,30].…”
Section: Discussionsupporting
confidence: 93%
“…Longer length of stay, comorbidities, postural hypotension and mental health condition such as depression and delirium increase the risk of PSI in older patients because of their increased requirement for care. Adamuz et al’s 2020 . A systematic review using data from eight studies conducted in the United States, United Kingdom, New Zealand, Canada and Australia showed that most PSI resulted in little or no disability, a significant minority (median 14%) caused permanent disability (7%) or death (7%) (De Vries et al 2008 ).…”
Section: Discussionmentioning
confidence: 98%
“…Previous research has suggested that the risk of an adverse event increases with patient complexity 26 and length of stay. 25 Due to their clinical profile and utilization pattern, high-need patients are therefore particularly vulnerable, with an adverse event risking further deterioration of health status and adding complexity to patient care.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events almost always occur in combination with an underlying health condition 24 and correlate with length of stay. 25 The overall risk for an adverse event appears highest for complex and more clinically severe types of patients, 26 with a study from Australia estimating that each additional night in hospital increases the risk of an adverse event between 0.5% and 1.6%. 25 It is therefore possible that the burden of adverse events is disproportionately affecting high-need patients (i.e., patients with high utilization of health care services due to a complex disease profile), considering their higher frequency of hospitalization, characterized by complex care needs and longer length of stay.…”
Section: Introductionmentioning
confidence: 99%